Protein kinase C mediates x-ray inducibility of nuclear signal transducers EGR1 and JUN. - Hallahan, D E (1991)
The cellular response to ionizing radiation includes growth arrest and DNA repair followed by proliferation. Induction of immediate early response genes may participate in signal transduction preceding these phenotypic responses. We analyzed mRNA expression for different classes of immediate early genes (JUN, EGR1, and FOS) after cellular x-irradiation. Increased expression of the EGR1 and JUN genes was observed within 0.5-3 hr following x-ray exposure. Preincubation with cycloheximide was associated with superinduction of JUN and EGR1 in x-irradiated cells. Inhibition of protein kinase C activity by prolonged stimulation with phorbol 12-myristate 13-acetate or the protein kinase inhibitor H7 prior to irradiation attenuated the increase in EGR1 and JUN transcripts. FOS expression was not coregulated with that of EGR1 following x-irradiation, suggesting a distinct regulatory pathway of this gene as compared with its regulation following serum and phorbol ester. These data implicate the EGR1 and JUN proteins as signal transducers during the cellular response to radiation injury and suggest that this effect is mediated in part by a protein kinase C-dependent pathway.